2020
DOI: 10.3389/fpubh.2020.00043
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation for Regulatory Application: A Content Analysis of FDA Risk Evaluation and Mitigation Strategies Assessment Plans (2014–2018) Using RE-AIM

Abstract: Background: Risk Evaluation and Mitigation Strategies (REMS) are safety programs that U.S. Food and Drug Administration can require to ensure a drug's benefits outweigh its risks and can be considered public health interventions. FDA's 2019 draft Guidance for Industry on REMS Assessments encourages the development of "novel methods for assessing REMS [to] help advance the science of post-market assessment of effectiveness of risk mitigation strategies." Objective: To characterize REMS assessment plans using RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Because many REMS are complex and the risks that they are designed to mitigate differ from one REMS to the next, REMS programs vary in their design, 42 a feature that affects their assessments. Toyserkani and colleagues conducted a content analysis of 18 REMS assessments plans using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework 43,44 . Across the five domains of the RE‐AIM framework, they found that most assessments measured Reach (the extent to which the REMS intervention reached the intended stakeholders) and Effectiveness (the extent to which safe‐use conditions were followed and the extent to which the intended safety‐related health outcome or a surrogate thereof was attained).…”
Section: Overview Of Assessments Of Risk Evaluation and Mitigation Strategiesmentioning
confidence: 99%
“…Because many REMS are complex and the risks that they are designed to mitigate differ from one REMS to the next, REMS programs vary in their design, 42 a feature that affects their assessments. Toyserkani and colleagues conducted a content analysis of 18 REMS assessments plans using the Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE‐AIM) framework 43,44 . Across the five domains of the RE‐AIM framework, they found that most assessments measured Reach (the extent to which the REMS intervention reached the intended stakeholders) and Effectiveness (the extent to which safe‐use conditions were followed and the extent to which the intended safety‐related health outcome or a surrogate thereof was attained).…”
Section: Overview Of Assessments Of Risk Evaluation and Mitigation Strategiesmentioning
confidence: 99%
“…Studies varied in terms of purpose. Two studies aimed to compare the content of plans for programs to minimize drug-safety risks and the corresponding regulatory guidance pertaining to the implementation and evaluation of such programs [40,41]. Three other studies evaluated the uptake of a drug or drug-related innovation and/or barriers and facilitators to its adoption (i.e., HIV prophylaxis treatment, new patientcentered drug labeling guidelines, statin prescribing and use) [21,42,43].…”
Section: Study Purposementioning
confidence: 99%
“…[Insert Table 3 here] Studies varied in use across implementation phases and speci c application. Six studies reported using the IS TMF after implementation of the intervention [40,41,43,44,46,47]. Three of the post-implementation studies [43,44,46] used the TMFs to guide the planning of data collection tools and analysis.…”
Section: Use Of Implementation Tmfsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actions required can involve several stakeholders and moving parts. In addition, it can be hard to clearly see the connection to effectiveness and impact of these programs [4][5][6][7][8] , which hampers buy-in and therefore compliance. 9,10 The Food and Drug Administration (FDA) Amendments Act in 2007 gave the FDA authority to require drug manufacturers to provide additional information, or REMS, to ensure the benefits of using a medication would outweigh the risks, as the FDA deemed appropriate.…”
Section: The Background and Challenges With Risk Evaluation And Mitigation Strategies (Rems) Programsmentioning
confidence: 99%